Antibodies Enhance the Suppressive Activity of Extracellular Vesicles in Mouse Delayed-Type Hypersensitivity - Katarzyna Nazimek; Eugenio Bustos-Morán; Noelia Blas-Rus; Bernadeta Nowak; Justyna Totoń-Żurańska; Michał T. Seweryn; Paweł Wołkow; Olga Woźnicka; Rafał Szatanek; Maciej Siedlar; Philip W. Askenase; Francisco Sánchez-Madrid; et al. (MDPI AG, 2021)
Previously, we showed that mouse delayed-type hypersensitivity (DTH) can be antigen-specifically downregulated by suppressor T cell-derived miRNA-150 carried by extracellular vesicles (EVs) that target antigen-presenting macrophages. However, the exact mechanism of the suppressive action of miRNA-150-targeted macrophages on effector T cells remained unclear, and our current studies aimed to investigate it. By employing the DTH mouse model, we showed that effector T cells were inhibited by macrophage-released EVs in a miRNA-150-dependent manner. This effect was enhanced by the pre-incubation of EVs with antigen-specific antibodies. Their specific binding to MHC class II-expressing EVs was proved in flow cytometry and ELISA-based experiments. Furthermore, by the use of nanoparticle tracking analysis and transmission electron microscopy, we found that the incubation of macrophage-released EVs with antigen-specific antibodies resulted in EVs' aggregation, which significantly enhanced their suppressive activity in vivo. Nowadays, it is increasingly evident that EVs play an exceptional role in intercellular communication and selective cargo transfer, and thus are considered promising candidates for therapeutic usage. However, EVs appear to be less effective than their parental cells. In this context, our current studies provide evidence that antigen-specific antibodies can be easily used for increasing EVs' biological activity, which has great therapeutic potential.